THE QURâ€™ANIC JESUS: ISA AL-MASIH IN THE QURâ€™AN - Ghafur, Waryono Abdul; Prasojo, Zaenuddin Hudi; Bin Haji Masri, Mohammed Sahrin (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2019)
The perspective on Isa al-Masih or Jesus has been one point of separation and a source of endless tension between Islam and Christianity. While Western tradition believes that Isa al-Masih is the son of God, Islam ensures that Isa is the son of a human being, a servant of God or a prophet and a messenger of God. This paper is not intended to resolve this debate, but through a thematic study by examining verses that reveal about Isa al-Masih in any verses in the Qur?an, wants to show that despite theological differences in the views of Isa al-Masih between Islam and Christianity cannot be avoided. However the meeting points between Islam and Christianity is very strong and that is in the Qur?an called Kalimatun sawa? which makes both emphasize peace rather than conflict. Isa al-Masih is seen by Christians and Muslims as a respected figure and has a prophetic mision of freeing the weak and oppressed people. Therefore, in Islamic tradition, Isa al-Masih is considered as the apostle of ulul azmi or the liberator Prophet.